Analisis Faktor-Faktor yang Mempengaruhi Keberadaan Kawasan Pemukiman Kumuh di Kelurahan Tembung Kecamatan Medan Tembung - Sakira Putri Manurung; Maria Dwi Sianipar; Nadratul Aini Lubis; Tamim Hasyimi; Egi Ateta Barus; Elfayetti Elfayetti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The purpose of this study was to analyze the factors that influence the existence of slums in Tematta Dorf district, Medan. Slums are one of the serious problems in urban development that affect the quality of life of the community. The method used in this study is a quantitative method with a descriptive approach and multiple regression analysis. Respondents consisted of field surveys, interviews, data received through documents, and residents and relatives. The results of the study indicate that several main factors that influence the existence of slums in this area are income levels, population density, availability of basic infrastructure, and spatial politics. Limited infrastructure and low community income have the most important impacts of these factors. This study concludes that efforts to overcome regional slums require a multidimensional approach by improving infrastructure, spatial sustainability planning and strengthening the community economy.